Firm-specific determinants of listed Portuguese firms having PPP concessions contracts : An exploratory research - Caetano, Tânia Filipa Teixeira (2015)
This research examines the firm-specific determinants of listed Portuguese firms having Public Private Partnerships -Concessions Contracts (PPP-CC) compared to those who haven´t got. Based on accounting standards and other specific legislation regarding PPP-CC, a set of determinants was tested in order to find some firm specific characteristics that are linked with the probability of having those forms of arrangements. The sample under analysis covers a period of four years, between 2008 and 2011. This sample contains 33 companies that give a total of 132 firm-year observations that are analyzed using a binary logistic regression model. The results of this research show that, as expected, larger firms, more leveraged and with higher level of Working Capital have more probability of having PPP-CC. On the other hand, Asymmetric Information, which was expected to have a negative impact, has shown to affect positively the probability of having PPP-CC. Furthermore, the results put in evidence, as expected, that growing opportunities is not a distinguishing characteristic between these two groups of companies. This research contributes to the scarce but growing literature on PPP-concession subject, that in the last few years have been drawing some attention from the Portuguese media and the general public.